Relativity of Hexachloroplatinate(IV) in Alkaline Medium: Influence of Ionic strength, Dielectric Constant and Temperature on the Reaction - Kali Sen Gupta, Kalayan; Ara Begum, Bilkis (Asian Journal of Chemistry, 2010)
The reactivity of hexachloroplatinate(IV) in alkaline medium wasstudied in the temperature range 308-323 K. The reaction is first orderwith respect to [PtCl62- ] and [OH- ]. The rate increases with the increasein dielectric constant as well as ionic strength of the medium. The valuesof ΔH≠ and ΔS≠ are 34 ± 4 kJ mol-1 and -195 ± 14 J K-1 respectively. Thereaction appears to proceed through the replacement of CI- in the coordinationsphere of hexachloroplatinate(IV) by OH- to give products.